2002
DOI: 10.4269/ajtmh.2002.66.260
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grapefruit juice or cimetidine coadministration on albendazole bioavailability.

Abstract: Abstract. The assumed metabolic breakdown of albendazole by mucosal CYP3A4 enzymes was studied by coadministering albendazole (10 mg/kg) with grapefruit juice. Concentrations of albendazole sulfoxide (ABZSX), the active metabolite of albendazole, were compared with those after albendazole was administered with water, a fatty meal, or grapefruit juice plus cimetidine (10 mg/kg). In comparison to water, maximum ABZSX concentration (C max ) was enhanced 6.5-fold by a fatty meal (from 0.24 ± 0.09 mg/l to 1.55 ± 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
2
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 19 publications
(18 reference statements)
3
53
2
2
Order By: Relevance
“…Modifications in bioavailability have been observed with the co-ingestion with a fatty meal, which more than triples the peak concentration (Cmax) of albendazole sulfoxide, as does grapefruit ingestion. 11,15 While there are no published studies of albendazole pharmacokinetics specifically in individuals with cirrhosis, observations in individuals with extrahepatic obstruction have shown a doubling in the Cmax and an increased half-life (T 1/2 ). 16 Studies in healthy volunteers also demonstrate albendazole-induced hepatic oxidizing enzymatic induction with a reduced T 1/2 and area under the curve in multi-dosing studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modifications in bioavailability have been observed with the co-ingestion with a fatty meal, which more than triples the peak concentration (Cmax) of albendazole sulfoxide, as does grapefruit ingestion. 11,15 While there are no published studies of albendazole pharmacokinetics specifically in individuals with cirrhosis, observations in individuals with extrahepatic obstruction have shown a doubling in the Cmax and an increased half-life (T 1/2 ). 16 Studies in healthy volunteers also demonstrate albendazole-induced hepatic oxidizing enzymatic induction with a reduced T 1/2 and area under the curve in multi-dosing studies.…”
Section: Discussionmentioning
confidence: 99%
“…10 Albendazole undergoes virtually 100% first-pass metabolism in the liver, and is rapidly converted to albendazole sulfoxide by both the microsomal flavin mono-oxidase and P450 CYP3A enzymes. 11 It then undergoes partial further metabolism to albendazole sulfone via a separate P450-dependent enzyme CYP2C. 12,13 Pharmacokinetic studies have demonstrated significant intra-individual and inter-individual variation in peak dose (Cmax) following albendazole ingestion among healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increased systemic bioavailability of albendazole was reported when the drug co-administered with a fatty meal [11], fruit juice [12], cosolvent [13], or with surfactants [14].…”
Section: Albendazole (Abz) Methyl[ 5-(propylthio)-1-h-benzimidazol-2mentioning
confidence: 99%
“…To inhibit CYP3A4 isozyme-related ABZSX degradation, albendazole was coadministered with cimetidine. However, this caused a 52% decrease in ABZSX C max values (probably due to inhibition of gastric acid secretion) (15,17), suggesting that absorption is pH dependent. When coadministered with grapefruit juice, the ABZSX C max was enhanced 3.2-fold, probably due to inhibition of the intraluminal degradation of albendazole by CYP3A4 enzymes (15).…”
mentioning
confidence: 99%
“…When combined with a fatty meal, administration of albendazole sulfoxide (ABZSX) increased the maximum concentration of drug in serum (C max ) 4.5-to 9-fold (1,7,12,15). To inhibit CYP3A4 isozyme-related ABZSX degradation, albendazole was coadministered with cimetidine.…”
mentioning
confidence: 99%